GAINING COMPETITIVE ADVANTAGE THROUGH MULTI-SOURCE FEEDBACK PERFORMANCE APPRAISAL - S. Suhana (Universitas Trunojoyo Madura, 2006)
The article discusses about gaining competitive advantageof a company through multi-source feedback performance appraisal.In a turbulence and high competitive environment, a company will facemany obstacles to run its business. In order to be able to sustain itsgrowth, it must have competitive advantages. Through human resourcemanagement, a company can have unique, scarce and difficult to imitatecompetencies. Performance appraisal is one of aspects of humanresource management practices. Traditional top-down approach inperforming appraisal is not sufficient anymore to accommodate thechanges of organizational need (structure, culture, etc). Multi-sourcefeedback if implemented well will be a good alternative to fulfill theneed of organization performance appraisal. The success of multi-source feedback implementation will give a company competitiveadvantage.